2022
DOI: 10.31083/j.fbl2703090
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic and Metabolomic Analyses of Plasma Reveal the Novel Biomarker Panels for Thyroid Dysfunction

Abstract: Background: Thyroid dysfunction, including hypothyroidism (THO) and hyperthyroidism (THE), commonly arise from pathological processes in the thyroid gland. The current diagnosis of thyroid dysfunction varies because of the age and sex of the patients. The aim of this study was to explore novel candidate biomarker panels for hypothyroidism and hyperthyroidism screening with mass spectrometry and bioinformatics. Methods: Plasma samples were collected from 15 THE patients, 9 THO patients, and 15 healthy controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…This mirrors ndings in experimentally induced and naturally occurring human hyperthyroidism, where alterations in metabolomic signatures persist despite returning to the euthyroid state. [12][13][14][15] The metabolomic signature of hyperthyroid cats in our study corroborated altered cholesterol and steroid hormonogenesis observed in hyperthyroid humans. [16][17][18] Key components of the mevalonate pathway, the hydroxy fatty acids mevalonate and mevalonolactone, are essential for cholesterol biosynthesis.…”
Section: Discussionsupporting
confidence: 77%
“…This mirrors ndings in experimentally induced and naturally occurring human hyperthyroidism, where alterations in metabolomic signatures persist despite returning to the euthyroid state. [12][13][14][15] The metabolomic signature of hyperthyroid cats in our study corroborated altered cholesterol and steroid hormonogenesis observed in hyperthyroid humans. [16][17][18] Key components of the mevalonate pathway, the hydroxy fatty acids mevalonate and mevalonolactone, are essential for cholesterol biosynthesis.…”
Section: Discussionsupporting
confidence: 77%
“…The proteomic analysis of the plasma samples was performed, as described previously. 17 SDS free lysate (7 M urea, 2 M thiourea, 20 mM Tris–HCl, pH 8.0) was added to 100 μL of the plasma sample, and finally to make up a total volume of 1 mL; then the proteins were reduced with 10 mM DTT for 30 minutes at 37 °C and alkylated with 55 mM iodoacetamide for 30 minutes at room temperature. Using a C18 SPE (solid phase extraction) column, protein enrichment was conducted and the eluate was frozen and dried for further treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction of metabolites followed the following steps. 17 After being thawed slowly at 4 °C, each plasma sample (100 μL) was placed in 96-well plates. Then, 300 μL of extraction solution (methanol : ACN = 2 : 1, v : v, −20 °C precooling) and 20 μL of the internal standard were added to each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Samples of plasma were processed according to the previously described procedure with modifications [ 22 ]. Briefly, 100 μg of the protein was purified by methanol/chloroform precipitation.…”
Section: Methodsmentioning
confidence: 99%